PPH 21 Calculation Application Program For Web-Based Employee Payroll - Sadiyah, Khalimatus; Andhita, Miranti; Oktavia, Oktavia; Suciyono, Nanang (Journal of Economics, Management, and Entrepreneurship, 2023)
STMIK Mardira Indonesia now employs a basic system, Microsoft Excel, to manage staff salaries. However, this system needs more integration with a database for storage purposes. Administrators are concerned about the potential risks associated with manually storing data, including a high likelihood of data loss and other issues, such as miscalculations due to incomplete data entry. Furthermore, the lack of a program to compute Income Tax Article 21 (PPH 21), essential information employees require to comprehend the deductions applied to their earned income, is apparent. This study aims to develop a web-based application for calculating employee payroll, explicitly focusing on PPH 21 calculations. The research methodology utilized in this concluding project is descriptive. The system development method employs the Waterfall approach, incorporating Object-Oriented Analysis and Design (OOAD) for the analysis and design of the proposed system. The system design utilizes a web programming language, specifically the CodeIgniter framework, in conjunction with a MySQL database. The research findings indicate that a web-based employee payroll system using the PPH 21 calculation program has been effectively constructed. This technology is available to employees, making it easier to administer payroll and providing employees with information on the amount of PPH 21 deductions. Suggestions for advancing the web-based employee payroll system, including the PPH 21 calculation tool, involve streamlining the system to improve efficiency.